(untitled) (Minerva, 2019)
Review: Mª Pilar Fernández – Emiliano Fernández – Teresa Martínez (eds.), Est hic varia lectio, la lectura en el mundo aniguo, Ediciones Universidad de Salamanca, 2008. 202 pp. ISBN. 978-84-7800-301-3